Structural analysis of biofilms and pellets of Aspergillus niger by confocal laser scanning microscopy and cryo scanning electron microscopy - Villena, GK (2010)
This work was supported by INCAGRO (Ministry of Agriculture, Peru) and CONCYTEC (Ministry of Education, Peru). The authors wish to thank CERTINTEX (Lima, Peru) for the use of its SEM facilities, and Mr. Gianangelo Nava (CERTINTEX) for his SEM technical assistance.